INFLUENCE OF WATER SOLUBLE FERTILIZERS ON GROWTH IN BRINJAL HYBRID (Solanum melongena L.) - ANBURANI, A. (Journal of Plant Stress Physiology)
In the present study, a field investigation was carried out to study the effect of water soluble fertilizers on growth and yield parameters of brinjal hybrids due to application of various levels of water soluble fertilizer. Foliar spray of NPK with 5 and 7 sprays, each starting from 30 DAT at 10 days interval, formed twenty treatments in two hybrids. The results showed that among the two different concentrations of foliar applied nutrients, 7 sprays of 1% NPK (19:19:19) along with 100 per cent recommended dose of fertilizer (200:150:100 kg ha-1) recorded the highest plant height, number of primary branches, secondary branches, stem girth, number of leaves per plant, leaf area.